Inovasi Program Pos Pemberdayaan Keluarga Posdaya Asli Pandanwangi - Rofieq, Mochammad; Siswati, Aris; Nugraha, Ginanjar Indra Kusuma (STIE Malangkucecwara, 2024)
The Family Empowerment Post (Posdaya) is a forum for friendship, advocacy, communication, education and an integrated forum for strengthening family functions. This forum is formed from, by and for families and communities. Posdaya membership is voluntary and not associated with any particular political party, ethnicity, or religion. Because Posdaya activities are empowering all family functions, namely Education, Health, Entrepreneurship, Environment, Religion and Culture, therefore innovation is very much needed in carrying out its work program. Posdaya ASLI is one of the Posdayas formed by community groups in the RW. 14 Kelurahan Pandanwangi Kecamatan Blimbing, Malang City. The purpose of this activity is to innovate the empowerment program at Posdaya ASLI, especially the production of Jilbab Syar'i